CONVERGENCE OF INCOME AMONG PROVINCES IN INDONESIA,1984-2008: A PANEL DATA APPROACH - Kharisma, Bayu; Saleh, Samsubar (Journal of Indonesian Economy and Business, 2013)
This paper aims to analyze the income dispersion and test both absolute convergenceand conditional convergence of income among 26 provinces in Indonesia during 1984-2008 using static and dynamic panel data approach. Using the Ï convergence analysisindicated that income dispersion measured by coefficient variation occurred in 1984-2008generally experienced fluctuation. Factors influencing income dispersion rate were theimpact of the economic crisis, the period of fiscal decentralization in Indonesia, the impactof the Bali bombing, impact of rising fuel prices in October 2005 and the earthquake inJogjakarta and Central Java. Dynamic panel data estimation with system GMM producedan efficient and consistent estimator to overcome the problems of instrument validity. Inaddition, it is also dedicated to minimize the risk of bias due to endogeneity problem.There was a strong indication of the existence of absolute convergence and conditionalconvergence among 26 provinces in Indonesia during 1984-2008. Thus, there wasevidence that the economy of poorer provinces tends to grow faster compared to the moreprosperous provinces, and this progress meant that there was a tendency to catch up.Based on the system GMM estimation, it is found that the provinces in Java havefasterspeed of convergence comparatively to those outside Java.Keywords: Income dispersion, absolute convergence, conditional convergence, systemGMM